Points of View from Above - Chías Navarro, Pilar; Giordano, Andrea; Zerlenga, Ornella (diségno, 2023)
In the most general sense, ‘point of view’ means point from which something is imagined to be observed (an object, an architecture, a landscape, etc.). The concept of ‘point of view’ is in fact synonymous in terms of ‘angulation’, ‘visual angle’, ‘perspective’ and can correspond to a point that is both physical and figurative. [read more]